Strategi Pengelolaan Wisata Pantai Cemara Kembar Kabupaten Serdang Bedagai (Tourism Management Strategy of Cemara Kembar Beach in Serdang Bedagai District) - Akmila Akmila; Pindi Patana; Yoes Soemaryono (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
The tourism area is dependent on its management to give huge benefit for development, so it needs strategies dan local comunnities participation. This research aimed to determine the tourism suitability and the proper tourism management strategies of Cemara Kembar Beach. This study was conducted in april-may 2016 in Cemara Kembar Beach, Sei Nagalawan Village, Serdang Bedagai District. Tourism suitability was measurred in situ while the management strategy was analyzed by SWOT analysis. Suitability index value of Cemara Kembar Beach tourism area is 87,1% which is in the very appropriete category. Based on SWOT analysis, Cemara kembar beach is in Quardan 1 which is the S-O (Growth Strategy) strategy. This strategy allows to utilize the strength and opportunity to gain benefits.Keyword: Cemara Kembar Beach , SWOT, Tourism Management Strategy